Study on Stress-Strain Characteristics of Pipeline-Soil Interaction under Ground Collapse Condition - Xiaohui Liu; Zhizhong Sun; Jianping Zhu; Yingchao Fang; Yanglian He; Yuchen Pan (Geofluids)
Ground collapse is one of the main geological disasters affecting the safe operation of oil and gas pipelines. Studying the stress-strain characteristics of pipe-soil interaction under ground collapse has an important guiding role for the prevention of ground collapse and the safety protection of pipelines. The current results are mostly concentrated in a single theory or the stress of the pipeline itself, which cannot fully consider the pipe-soil interaction. In this paper, ABAQUS is used to establish the finite element geometric model. Considering the pipeline and the surrounding geological environment conditions, the study is carried out from five aspects: the length of the collapse area, the thickness of the cover layer, the buried depth of the pipeline, the diameter of the pipeline, and the thickness of the pipeline. The displacement of the pipeline soil, the deformation of the pipeline, and the characteristics of the pipeline stress are analyzed, and the variation law is determined through the development trend of the pipeline stress and strain. At the same time, by fitting and analyzing the relationship between the span of different subsidence areas, the thickness of the cover layer, the buried depth of the pipeline, the diameter of the pipeline, the thickness of the pipeline, and the maximum deformation of the pipeline, the reference value of the maximum subsidence displacement of the pipeline under the action of ground collapse is proposed. The work has practical application value for pipeline monitoring, early warning, and disaster management.